Randomized controlled study in pregnancy on treatment of marked hyperglycemia that is short of overt diabetes. (29th August 2015) - Fadl, Helena E.; Gärdefors, Susanne; Hjertberg, Ragnhild; Nord, Eva; Persson, Bengt; Schwarcz, Erik; Åman, Jan; Östlund, Ingrid K.; Hanson, Ulf S.B.
Abstract Introduction A randomized multicenter study was conducted in the Stockholm‐Örebro areas in Sweden to evaluate how treatment aiming at normoglycemia affects fetal growth, pregnancy and neonatal outcome in pregnant women with severe hyperglycemia. Material and methods Pregnant women with hyperglycemia defined as fasting capillary plasma glucose <7.0 mmol/L and a two‐hour plasma glucose value ≥10.0 and <12.2 mmol/L following a 75‐g oral glucose tolerance test (OGTT) diagnosed before 34 weeks of gestation were randomized to treatment (n = 33) or controls (n = 36). Women assigned to the control group were blinded for the OGTT results and received routine care. The therapeutic goal was fasting plasma glucose 4–5 mmol/L, and <6.5 mmol/L after a meal. Primary outcomes were size at birth and number of large‐for‐gestational age (>90th percentile) neonates. Secondary outcomes were pregnancy complications, neonatal morbidity and glycemic control. Results The planned number of participating women was not reached. There was a significantly reduced rate of large‐for‐gestational age neonates, 21 vs. 47%, P < 0.05. Group differences in pregnancy complications and neonatal morbidity were not detected because of limited statistical power. In total, 66.7% of the women in the intervention group received insulin. Of all measured plasma glucose values, 64.1% were in the target range, 7.2% in the hypoglycemic range and 28.7% above target values. There were no cases of severe hypoglycemia. Conclusions Aiming for normalized glycemia in a pregnancy complicated by severe hyperglycemia reduces fetal growth but is associated with an increased rate of mild hypoglycemia.